On the behavior and performance of chaos driven PSO algorithm with inertia weight - Pluhacek, Michal; Senkerik, Roman; Davendra, Donald; Kominkova Oplatkova, Zuzana; Zelinka, Ivan (Computers & mathematics with applications (1987), 2013)
In this paper, the utilization of chaos pseudorandom number generators based on three different chaotic maps to alter the behavior and overall performance of PSO algorithm is proposed. This paper presents results of testing the performance and behavior of the proposed algorithm on typical benchmark functions that represent unimodal and multimodal problems. The promising results are analyzed and discussed.